2013
DOI: 10.7567/apex.6.041001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mg Doping Efficiency in P-Type GaN by Indium-Surfactant-Assisted Delta Doping Method

Abstract: An indium-surfactant-assisted delta doping method is reported to enhance the hole concentration and doping efficiency of Mg-doped p-type GaN grown by metal organic chemical vapor deposition. The hole concentration is increased to 1.5×1018 cm-3 by using this method, which is 92% higher than that of conventional delta doping. This higher carrier concentration leads to an improved doping efficiency of 12%. Secondary ion mass spectroscopy reveals that the Mg incorporation is increased by the In surfactant. Photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…Further experiments need to be performed to clarify the origin of the activation energy reduction. Moreover, the lower rate parameter of α τ = 39 659 obtained in the p‐type GaN sample grown with In surfactant indicates a decreased (D 0 , Mg 0 ) transition rate in this case, which can be ascribed to the fewer neutral Mg acceptors in the p‐type GaN, consistent with the analysis from the reduction of UVL band intensity at 30 K. These optical analysis results are in good agreement with those obtained from the temperature‐dependent Hall‐effect analysis , in which the Mg activation energies are 130 meV and 113 meV for the Mg‐δ‐doped samples grown without and with In surfactant, respectively. Moreover, it was also found that the compensation ratio C decreases from 35% to 24% when the In surfactant is employed, suggesting a suppression of V N .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Further experiments need to be performed to clarify the origin of the activation energy reduction. Moreover, the lower rate parameter of α τ = 39 659 obtained in the p‐type GaN sample grown with In surfactant indicates a decreased (D 0 , Mg 0 ) transition rate in this case, which can be ascribed to the fewer neutral Mg acceptors in the p‐type GaN, consistent with the analysis from the reduction of UVL band intensity at 30 K. These optical analysis results are in good agreement with those obtained from the temperature‐dependent Hall‐effect analysis , in which the Mg activation energies are 130 meV and 113 meV for the Mg‐δ‐doped samples grown without and with In surfactant, respectively. Moreover, it was also found that the compensation ratio C decreases from 35% to 24% when the In surfactant is employed, suggesting a suppression of V N .…”
Section: Resultssupporting
confidence: 88%
“…Previous SIMS results have shown that the incorporation of Mg dopant can be obviously enhanced by the In surfactant . The Mg concentration increased from 8.8 × 10 18 cm −3 to 1.2 × 10 19 cm −3 when using indium‐surfactant‐assisted δ‐doping, which plays a key role in the enhancement of hole concentration.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The hole concentration was significantly increased, contributing most to the enhanced electrical conductivity with a resistivity comparable to those of the state-of-the-art p-GaN. 27,28 Besides, the hole mobility of the PTGF sample is also slightly higher than that of the control sample, despite the higher hole concentration. This is likely due to the reduced dislocation scattering.…”
Section: Resultsmentioning
confidence: 96%